Reciprocal cooperation networks managed by IICA for the generation and transfer of agricultural technology - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
Series Publicación Miscelánea A1/SC (IICA) no. 90-07.